2014
DOI: 10.3354/meps10862
|View full text |Cite
|
Sign up to set email alerts
|

Effects of simulated fish predation on small colonies of massive Porites spp. and Pocillopora meandrina

Abstract: The effects of corallivory on small colonies of massive Porites spp. (< 5 cm diameter) and Pocillopora meandrina (< 7 cm high) were explored in situ on shallow reefs in Moorea, French Polynesia. Experiments were conducted to test the hypothesis that corals respond equally to damage caused by single bites of fishes belonging to 3 functional feeding guilds defined as excavators, scrapers, and browsers, which damage corals in different ways. While recovering from damage, massive Porites spp. grew 24 to 43% faster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 61 publications
0
11
0
Order By: Relevance
“…The extent of damage often mediates the effects of corallivory on coral growth. Cameron and Edmunds (2014) observed that massive Porites and Pocillopora meandrina growth rates declined with more damaging modes of simulated fish corallivory (growth rates: browsed > scraped > excavated). Yet protection from corallivores with various foraging strategies can increase coral growth (Cox, 1986;Lenihan et al, 2011;Shantz et al, 2011), suggesting that even browsing corallivory has observable effects on coral growth (Shaver et al, 2017;Clements and Hay, 2018;Hamman, 2018).…”
Section: Growthmentioning
confidence: 97%
“…The extent of damage often mediates the effects of corallivory on coral growth. Cameron and Edmunds (2014) observed that massive Porites and Pocillopora meandrina growth rates declined with more damaging modes of simulated fish corallivory (growth rates: browsed > scraped > excavated). Yet protection from corallivores with various foraging strategies can increase coral growth (Cox, 1986;Lenihan et al, 2011;Shantz et al, 2011), suggesting that even browsing corallivory has observable effects on coral growth (Shaver et al, 2017;Clements and Hay, 2018;Hamman, 2018).…”
Section: Growthmentioning
confidence: 97%
“…In O. patagonica , preferential translocation to recovering tissue proceeded from a distance of 4–5 cm, but this phenomenon does not occur in colonies that were fully or partially (30%–80%) bleached (Fine et al, ). The pace and completion of wound recovery are subject to the impacts of several intrinsic and extrinsic factors (such as colony size, wound size, wound location, temperature, disease state, sedimentation [as reviewed by Henry & Hart, and for example: Van Veghel & Bak, , Meesters, Noordeloos, & Bak, , Meesters, Wesseling, & Bak , Meesters, Pauchli, & Bak, , Nagelkerken & Bak, , Nagelkerken, Meesters, & Bak, , Kramarsky‐Winter & Loya, , Rotjan & Lewis, , Edmunds, , Denis et al, , Cameron & Edmunds, ]), which also have the potential to interact with energy sourcing and nutritional state. The type of damage inflicted may also play a role in how energy is regulated or redirected to recovery and other biological processes (DeFilippo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, both symbiotic state and lesion induction can alter the quantity and directionality of carbon translocation across a coral colony (Fine et al, 2002;Oren et al, 1997). In O. patagonica, preferential translocation to recovering tissue proceeded from a distance of 4-5 cm, but this phenomenon does not occur in colonies that were fully or partially (30%-80%) bleached (Fine et al, 2002 , Edmunds, 2009, Denis et al, 2011, Cameron & Edmunds, 2014), which also have the potential to interact with energy sourcing and nutritional state. The type of damage inflicted may also play a role in how energy is regulated or redirected to recovery and other biological processes (DeFilippo et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Rates of healing during Experiment 2 were 4.0% d -1 in ambient P CO2 and 3.9% d -1 in elevated P CO2 , which are similar to rates previously reported for massive Porites spp. For example, Cameron and Edmunds (2014) found that small colonies with single sites of excavation damage (each ~ 105 mm 2 and 2-5 mm deep) healed at ~ 2.5 % d -1 over 21 d, while Edmunds and Lenihan (2009) reported tissue healing of 4-5 % d -1 over 10 d for small colonies with lesions ~ 67 mm 2 and 1-2 mm deep.…”
Section: Discussionmentioning
confidence: 99%
“…Regeneration of tissue within the lesions was evaluated photographically as the rate at which new coral tissue filled in the damage (see Fig. 1 in Cameron and Edmunds, 2014). In Experiment 1, pictures of the lesions were recorded with a camera (Olympus 850 SW, 8 megapixels) prior to, and following, the incubation.…”
Section: Response Variablesmentioning
confidence: 99%